Cryptosporidium spp. and rotavirus gastroenteritis and change of incidence after rotavirus vaccination among children in Raparin Pediatrics Hospital, Erbil, Iraq (Faculty of Medicine Universitas Indonesia, 2017)
Background: Watery diarrhea is the most common medical problem among infants and young children, caused by different microbial etiology including Cryptosporidium spp. and rotavirus, which are usually misdiagnosed in conventional stool test. This study aimed to investigate the incidence of Cryptosporidium and rotavirus gastroenteritis among children in Erbil as well as evaluate the efficacy of rotavirus vaccination procedure applied in Erbil. Methods: Fecal specimens were collected from 400 children (boys and girls), aged one month to five years old, who attended Raparin Pediatrics Hospital in Erbil complaining from diarrhea, between January to August 2014. Modified Ziehl Neelsen technique and nested PCR were used for detection of cryptosporidiosis while rotavirus infection was detected by rapid CerTest. Results: Rate of detection of cryptosporidiosis was remarkably higher using PCR than Ziehl-Neelsen stain (0% versus 6%), and the infection was slightly higher among boys (6.25% vs 5.55%) and children ≤ 2 years (11.7%). The peak of infection reached during spring season (March and April) (9.5%). The detection rate of rotavirus was 32.0%, which was slightly higher among males (34.4% vs 30.0%) and in children between one to three years old (39.3%). The highest detection rate (38.6%) was recorded during winter season (January and February). The infection was significantly higher among non-vaccinated children (65.9% vs 14.1%; p<0.05). Conclusion: The incidence of cryptosporidiosis is declining. However, rotavirus gastroenteritis was relatively high among young children in Erbil. Rotateq vaccine significantly reduced the incidence of rotavirus infection.